Developing Reading Materials In Narrative Texts For Second Grade Students Of Fashion Design Department At SMK Negeri 8 Medan - Irda Silvia Sitepu; Willem Saragih; Rafika Dewi Nasution (Universitas Negeri Medan, 2018)
This study aims to develop reading materials needed for students at SMKN 8 Medan.The research was conducted by Research and Development (R & D) develop through six phases; gathering information and data, analyzing data, develop new materials, validating by experts, revising and final product. It was conducted at SMKN 8 Medan, especially grade XI. The data were gathered by administering interview to English teacher and distributing questionnaire to 27 students’ needs. The interview and questionnaire results prove that the students need English reading materials which contain the appropriate knowledge or topic with the Kemendikbud (Kementerian Pendidikan dan Kebudayaan), syllabus and students’ need. Thus, developing materials are narrative text, the narrative texts expose the texts about fashion which are adjacent with students’ need. The products have been validated by experts. The average scores are 4.6 or 92 % from English Lecturer and 4.75 or 95% or from English Teacher. It means the developing materials categorized as relevant or appropriate for students at SMN 8 Medan grade XI Keywords: Research and Development (R & D), Reading Materials, Vocational School, Fashion Design Program